Introduction to Futures and Options Markets / Second Edition - Hull John C (Prentice Hall International, 1995)
Preface, Introduction, Futures and Forward Markets, Mechanics of Futures and Forward Markets, The Determination of Forward and Future Prices, Hedging Strategies Using Futures, Interest-Rate Futures, Swaps, Option Markets, Mechanics of Option Markets, Basic Properties of Stock Options, Trading Strategies Involving Options, An Introduction to Binomial Trees, The Pricing of Stock Options Using Black-Scholes, Options on Stock Indices and Currencies, Options on Futures, Hedging Positions in Options and the Creation of Options Syntetically, Valuing Options Numerically Using Binomial Trees, Biases in the Black-Scholes Model, Interest-Rate Options, Answers to Quiz Questions, Index.